Search for a Higgs boson in the mass range from 145 to 1000 GeV decaying to a pair of W or Z bosons - Khachatryan, V; Sirunyan, AM; Tumasyan, A; Adam, W; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Flechl, M; Friedl, M; et al. (Springer Verlag, 2015)
A search for a heavy Higgs boson in the H → WW and H → ZZ decay channels is reported. The search is based upon proton-proton collision data samples corresponding to an integrated luminosity of up to 5.1 fb−1 at s√=7 TeV and up to 19.7fb−1 at s√=8 TeV, recorded by the CMS experiment at the CERN LHC. Several final states of the H → WW and H → ZZ decays are analyzed. The combined upper limit at the 95% confidence level on the product of the cross section and branching fraction exclude a Higgs boson with standard model-like couplings and decays in the range 145 < m H < 1000 GeV. We also interpret the results in the context of an electroweak singlet extension of the standard model.